CHARGING A CAR IN MOTION WIRELESSLY - Ležaić, Dario; Mihalić, Tihomir; Predin, Andrej (Journal of Energy Technology, 2024)
The concept is charging electric cars wirelessly, both stationary and in motion, via wireless modules prebuilt in roads or over energy towers that emit electrical energy through the air. The wireless charging of electric cars means there is a completely new obstacle for engineers: one that competes with conventional battery charging. The conventional charging of high capacity batteries is simple, because current travels along a wire that is made of metal and is a good conductor. However, how is it possible to transfer great amounts of electricity wirelessly through the atmosphere?
Keywords: wireless on-the-road-charging; Dynamic charging; Li-Air; wireless tower; car body panels as energy storage system